Networked Systems: 6th International Conference, NETYS 2018, Essaouira, Morocco, May 9-11, 2018, Revised Selected Papers - Podelski, Andreas; Taïani, François (Lecture Notes in Computer Science, 2019)
This book constitutes the thoroughly refereed conference proceedings of the 6th International Conference on Networked Systems, NETYS 2018, held in Essaouira, Morocco, in May 2018.The 22 full and 6 short papers presented together with 11 keynotes and 2 invited papers were carefully reviewed and selected from 85 submissions. They are organized in the following topics: distribution; concurrency; verification; networking; self-stabilization; security; graph; and middleware.